Chemotherapy impedes in vitro microcirculation and promotes migration of leukemic cells with impact on metastasis - Prathivadhi-Bhayankaram, Sruti V.; Ning, Jianhao; Mimlitz, Michael; Taylor, Carolyn; Gross, Erin; Nichols, Michael; Guck, Jochen; Ekpenyong, Andrew E. (Biochemical and Biophysical Research Communications, 2016)
Although most cancer drugs target the proliferation of cancer cells, it is metastasis, the complex process by which cancer cells spread from the primary tumor to other tissues and organs of the body where they form new tumors, that leads to over 90% of all cancer deaths. Thus, there is an urgent need for anti-metastasis therapy. Surprisingly, emerging evidence suggests that certain anti-cancer drugs such as paclitaxel and doxorubicin can actually promote metastasis, but the mechanism(s) behind their pro-metastatic effects are still unclear. Here, we use a microfluidic microcirculation mimetic (MMM) platform which mimics the capillary constrictions of the pulmonary and peripheral microcirculation, to determine if in-vivo-like mechanical stimuli can evoke different responses from cells subjected to various cancer drugs. In particular, we show that leukemic cancer cells treated with doxorubicin and daunorubicin, commonly used anti-cancer drugs, have over 100% longer transit times through the device, compared to untreated leukemic cells. Such delays in the microcirculation are known to promote extravasation of cells, a key step in the metastatic cascade. Furthermore, we report a significant (p < 0.01) increase in the chemotactic migration of the doxorubicin treated leukemic cells. Both enhanced retention in the microcirculation and enhanced migration following chemotherapy, are pro-metastatic effects which can serve as new targets for anti-metastatic drugs.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cancer; Cell mechanics; Daunorubicin; Doxorubicin; Metastasis; Microfluidics